Asymmetric Polynomial II

Algebra Level 3

x 3 10 x 2 25 x + 125 = 0 x^3-10x^2-25x+125=0

Let a > b > c a>b>c be the three solutions of the equation above. What is the value of a 2 b + b 2 c + c 2 a ? a^2b+b^2c+c^2a?


The answer is 500.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Ankush Tiwari
Mar 28, 2015

Let X = a 2 b + b 2 c + c 2 a X = a^2b +b^2c + c^2a and Y = a b 2 + b c 2 + c a 2 Y = ab^2 + bc^2 + ca^2 .

X Y = a b ( a b ) + b c ( b c ) + c a ( c a ) \Rightarrow X - Y = ab(a-b) + bc(b-c) + ca(c-a)

= a b ( a b ) + b c ( b c ) + c a ( c b + b a ) = ab(a-b) + bc(b-c) + ca(c-b +b-a)

= a b ( a b ) + b c ( b c ) c a ( b c ) c a ( a b ) = ab(a-b) + bc(b-c) -ca(b-c) - ca(a-b)

= ( a c ) ( a b ) ( b c ) = (a-c)(a-b)(b-c)

Now, using the definition of discriminant we have

Δ = ( a c ) 2 ( a b ) 2 ( b c ) 2 \Delta = (a-c)^2(a-b)^2(b-c)^2

The discriminant for the cubic polynomial p x 3 + q x 2 + r x + s px^3 + qx^2 + rx + s is given by

q 2 r 2 4 p r 3 4 q 3 s 27 p 2 s 2 + 18 p q r s q^2r^2 -4pr^3 -4q^3s - 27p^2s^2 + 18pqrs

On Solving we get Δ = 765625 \Delta = 765625

Since X Y X - Y is positive we have X Y X - Y = Δ = 875 \sqrt{\Delta} = 875

Also ( a + b + c ) ( a b + b c + a c ) = X + Y + 3 a b c (a + b+ c)(ab +bc+ac) = X + Y + 3abc

Using Vieta's Formula we get

X + Y = 125 X + Y = 125

Solving the 2 equations we get X = 500 X = 500 .

I don't know how to find discriminant of a cubic. Can you explain it, please?

Prakash Chandra Rai - 6 years, 2 months ago

Log in to reply

See this wikipedia page on discriminant.

Ankush Tiwari - 6 years, 2 months ago

Log in to reply

Thanks and nice solution

Prakash Chandra Rai - 6 years, 2 months ago

Excellent solution. Thank you for posting it.

Hosam Hajjir - 6 years, 2 months ago

Hello everyone, i'm still stuck trying to see why X - Y = (a-c)(a-b)(b-c), i can't really get how the last line of he "proof" works

Michele Franzoni - 2 years, 2 months ago

Log in to reply

collect terms with (b-c) and terms with (a-b), you get (bc-ca) (b-c) + (ab-ca) (a-b). Then collect - c from first bracket and a from third bracket you should get the factorization (a-b) (b-c) (a-c).

Ankush Tiwari - 2 years, 1 month ago
Vinay Chindu
Apr 10, 2015

a + b + c = 10 , a b + b c + c a = 25 , a b c = 125 a+b+c=10, ab+bc+ca=-25, abc = -125 .

Terms like a 2 b , b 2 c , c 2 a a^{2}b, b^{2}c, c^{2}a can be got by multiplying ( a + b + c ) (a+b+c) and ( a b + b c + c a ) (ab+bc+ca) .
( a + b + c ) ( a b + b c + c a ) = a 2 b + b 2 c + c 2 a + a b 2 + b c 2 + c a 2 + 3 a b c (a+b+c)(ab+bc+ca)=a^{2}b+b^{2}c+c^{2}a + ab^{2}+bc^{2}+ca^{2}+3abc .

Let X = a 2 b + b 2 c + c 2 a X = a^{2}b+b^{2}c+c^{2}a and Y = a b 2 + b c 2 + c a 2 Y = ab^{2}+bc^{2}+ca^{2} .
Straightforward algebraic manipulations give
X + Y = ( a + b + c ) ( a b + b c + c a ) 3 a b c X+Y = (a+b+c)(ab+bc+ca) - 3abc . Inserting the values, X + Y = 125 X+Y=125 .

Also, X Y = ( a b ) ( a c ) ( b c ) X-Y=(a-b)(a-c)(b-c) . Using the given constraint a > b > c a > b> c ,
X Y > 0 X-Y > 0 i.e. X > Y X> Y .

Multiplying X X & Y Y ,
X Y = a 3 b 3 + b 3 c 3 + c 3 a 3 + a b c ( a 3 + b 3 + c 3 ) + 3 ( a b c ) 2 XY=a^{3}b^{3}+b^{3}c^{3}+c^{3}a^{3}+abc(a^{3}+b^{3}+c^{3})+3(abc)^{2} .

It can be shown that
a 3 b 3 + b 3 c 3 + c 3 a 3 = ( a b + b c + c a ) 3 3 a b c ( a + b + c ) ( a b + b c + c a ) + 3 ( a b c ) 2 a^{3}b^{3}+b^{3}c^{3}+c^{3}a^{3} = (ab+bc+ca)^{3}-3abc(a+b+c)(ab+bc+ca)+3(abc)^{2} .
a 3 + b 3 + c 3 = ( a + b + c ) 3 3 ( a + b + c ) ( a b + b c + c a ) + 3 a b c a^{3}+b^{3}+c^{3} = (a+b+c)^{3}-3(a+b+c)(ab+bc+ca)+3abc .
Plugging the values, X Y = 12 × 12 5 2 XY=-12\times125^{2} .

X + Y = 125 X+Y=125 and X Y = 12 × 12 5 2 XY=-12\times125^{2} .
Solving X = 4 × 125 , Y = 3 × 125 X=4\times125, Y=-3\times125 .
X = 500 X=500 .

nice solution

ommkar priyadarshi - 5 years ago

How do you know that X 375 X \neq -375 ?

X = 375 , Y = 500 X = -375, Y = 500 is also a solution.

Jesse Nieminen - 4 years, 12 months ago

The value of X is greater than Y

vinay chindu - 4 years, 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...